Omega-3 fatty acid-derived resolvins and protectins in inflammation resolution and leukocyte functions: targeting novel lipid mediator pathways in mitigation of acute kidney injury - Hong, Song; Lu, Yan (Frontiers in Immunology, 2013)
Inflammation, in conjunction with leukocytes, plays a key role in most acute kidney injury (AKI). Non-resolving renal inflammation leads to chronic fibrosis and renal failure. Resolvin D series (RvDs) and E series (RvEs), protectins, and maresins (MaRs) are endogenous omega-3 fatty acid-derived lipid mediators (LMs) that potently promote inflammation resolution by shortening neutrophil life span and promoting macrophage (Mf) non-phelogistic phagocytosis of apoptotic cells and the subsequent exit of Mfs from inflammatory tissue. 14S,21R-dihydroxy docosahexaenoic acid (14S,21R-diHDHA), a Mf-produced autacrine, reprograms Mfs to rescue vascular endothelia. RvD1, RvE1, or 14S,21R-diHDHA also switches Mfs to the phenotype that produces pro-resolving interleukin-10. RvDs or protectin/neuroprotectin D1 (PD1/NPD1) inhibits neutrophil infiltration into injured kidneys, blocks toll-like receptor -mediated inflammatory activation of Mfs and mitigates renal functions. RvDs also repress renal interstitial fibrosis, and PD1 promotes renoprotective heme-oxygenase-1 expression. These findings provide novel approaches for targeting inflammation resolution and LMs or modulation of LM-associated pathways for developing better clinical treatments for AKI.